Optimizing Public Health through Community Service: Addressing Stunting and Open Defecation in Sidoarjo Regency - Sumasto, Hery; Rusyadi, Luthfi; Nur Kholifah, Siti; Triwiyanto, Triwiyanto; Suprihatin, Kusmini; Rohkmalia, Fitri; Maratus Sholikah, Siti; Islaha, Maria; Irianto Uripan, Koen (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Community service in health institutions needs to be guided by six pillars of health transformation, namely to overcome five priority diseases: tuberculosis, stunting, MCH, infectious diseases and non-communicable diseases. One of their focuses is Sidoarjo Regency, where they work closely with the Regional Government to improve public health. Some of the main problems in Sidoarjo Regency include the high rate of stunting and the practice of open defecation (ODF). There is a relationship between stunting and environmental sanitation, especially open defecation. Solutions to overcome this problem include the provision of healthy latrines to the community, increasing the capacity of Posyandu cadres, nutrition management, and promoting clean and healthy living behaviors. This community service activity is based on previous research relevant to stunting and ODF problems. The goal is to reduce stunting rates in five stunting locus villages, increase knowledge about clean and healthy living behaviors, and build 100 healthy family latrines. The method used is Theory, Practice, Follow-up (TPT) which involves training, field practice and advanced mentoring. Conclusion: with the construction of healthy latrines, there has been a decrease in the incidence of diarhe in children. Diarrhea in children is one of the latent causes of stunting rates. By implementing this strategy, it is hoped that a significant increase will be achieved in preventing and reducing stunting rates in Sidoarjo Regency